ANALISIS PENGENDALIAN INTERNAL KAS DENGAN PIUTANG TERHADAP EFEKTIVITAS ARUS KAS PADA PT. SINAR LESTARI UTAMA - Elidawati; Regina Jaya; Thomas Sumarsan Goh (STIE-PMCI, 2020)
Abstract.The company is currently developing rapidly, making the company expand its business in the business world. A company is an agent-organized by management, growth, and development that cannot be separated from economic law and the company's basic principles. The research method used in this research is a descriptive method that is a research method by studying the method used to describe or describe a collection of data or observations that have been made. The results showed that there are an organizational structure and job descriptions that reflect the duties and responsibilities of each employee from each department in the company and encourage employees to comply with existing regulations; there is also a division of functions related to authorization, monitoring, recording, and cash storage includes procedures related to corporate cash and the implementation of monitoring reports on cash receipts and distributions received by the Ministry of Finance. The company applies four credit limit conditions such as Capacity, Collateral, Character, and Conditions, so it is sufficient to make internal control of cash and receivables in PT. Sinar Lestari Utama is quite effective and efficient, intentionally or unintentionally providing effectiveness on the Cash Flow Statement Keywords: Internal Control, Cash, Account Receivable.